An Epidemiological Study on Burden of Psychological Morbidities and Their Determinants among Undergraduate Medical Students of a Government Medical College of Eastern India - Biswas, Bijit; Haldar, Anima; Dasgupta, Aparajita; Sembiah, Sembagamuthu; Karmakar, Anubrata; Mallick, Nazrul (Indian Journal of Community Health, 2018)
Background: Medical education can impose a significant amount of psychological stress and strain on undergraduates. In India, there are limited shreds of evidence regarding the magnitude of different psychological morbidities (i.e. stress, anxiety and depression) among medical undergraduates. Aims & Objectives: To find out the proportion of medical undergraduates suffering from psychological morbidities and their determinants. Material and Methods: It was a cross-sectional hospital-based analytical observational study conducted from July to November 2017. In total 327 undergraduate medical students of a government medical college of Kolkata were interviewed with a structured schedule comprising of socio-demographic, behavioural related questionnaire and DASS (Depression Anxiety Stress Scale) 21. Data were analysed by the Statistical Package for Social Sciences, SPSS (version 16). Results: The burden of stress, anxiety and depression among medical undergraduates were found out to be 33.0%, 26.9% and 21.1% respectively. The burden was much higher in females compared to males and increased with semester and age. In the multivariable model depression, anxiety and stress were significant predictors of each other along with sex, semester, both smoking and alcohol drinking, sleep adequacy and satisfaction with own educational performance. The variables in the multivariable models were explaining 29.0% of stress, 30.8% of anxiety and 32.2% of depression. Conclusion: The proportion of undergraduate medical students with psychological morbidity was found to be high in the current study. Smoking, alcohol drinking, sleep adequacy and educational satisfaction were some critical modifiable predictors of different psychological morbidities identified in the study.